Clinical, Hematological, and Histopathological Correlations in Women with Uterine Prolapse. A Multidimensional Gynecological Study - Muhammad Tariq Hamayun Khan, Amna Jahan, Maliha Asif, Tooba Ammar, Ikram Ul Haq, Abdul Karim Soomro (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Uterine prolapse is a common gynecological condition, especially among multiparous and postmenopausal women, characterized by downward displacement of the uterus. While clinically evident, the associated systemic and tissue-level changes remain under-investigated. This study aimed to explore the clinical presentation, hematological status, and histopathological alterations in women with uterine prolapse in a multidimensional framework. Methods: A cross-sectional study was conducted at tertiary care hospitals in Pakistan, specifically at the Burns and Plastic Surgery Centre, Hayatabad, Peshawar, and Jinnah Hospital, Lahore. A total of 100 women aged 30 to 75 years, diagnosed with varying grades of uterine prolapse classified according to the Pelvic Organ Prolapse Quantification (POP-Q) system, were enrolled. Clinical parameters such as age, parity, menopausal status, and duration of symptoms were documented. Hematological evaluations included complete blood count (CBC), focusing on hemoglobin concentration, total leukocyte count, and platelet count. Erythrocyte sedimentation rate (ESR) was assessed separately as an inflammatory marker, while C-reactive protein (CRP) was analyzed through chemical pathology. Histopathological examination of pelvic support tissues was performed in surgical cases (n=75) to evaluate fibromuscular integrity and vascular alterations. Results: The majority of patients were between 45 and 65 years and presented with Grade III or IV prolapse. Moderate to severe anemia was found in 68% of participants. Elevated ESR and CRP were noted in 54% of patients. Histopathological analysis revealed fibromuscular atrophy in 78%, chronic inflammation in 66%, stromal edema in 64%, and vascular congestion in 59% of surgical cases. Severity of prolapse correlated with histological and laboratory findings. Conclusion: Uterine prolapse is associated with structural degeneration, systemic inflammation, and hematological compromise. Integrated clinical, laboratory, and histological evaluation may enhance disease management. Keywords: Uterine prolapse, histopathology, anemia, ESR, CRP, pelvic floor dysfunction, fibromuscular atrophy.